Comparison of the effect of Dietary Approaches to Stop Hypertension diet and American Diabetes Association nutrition guidelines on lipid profiles in patients with type 2 diabetes: A comparative clinical trial. Issue 2 (4th June 2019) - Hashemi, Reza; Mehdizadeh Khalifani, Alireza; Rahimlou, Mehran; Manafi, Majid
Abstract : Aim: The present study aimed to compare the effects of the Dietary Approaches to Stop Hypertension (DASH) diet and American Diabetes Association (ADA) guidelines on the lipid profiles of patients with type 2 diabetes. Methods: In a 12‐week clinical trial, 80 patients with type 2 diabetes aged 18–65 years were randomly allocated into the case (n = 40) and control (n = 40) groups. The case group received the DASH diet and the control group consumed a dietary pattern in accordance with the ADA guidelines. Fasting blood samples were measured for triglyceride (TG), low‐density lipoprotein (LDL), total cholesterol (TC), high‐density lipoprotein (HDL), very low‐density lipoprotein (VLDL) and free fatty acid (FFA). Moreover, physical activity and 24‐hour dietary recall (24 hours) were assessed at baseline and end of the study. Results: The DASH diet and diabetic diet (in accordance with the ADA guidelines) for 12 weeks significantly decreased TG, TC and VLDL ( P < 0.05). FFA showed a significant decrease in both the groups, which was greater in the cases compared with the control group ( P = 0.049). Conclusions: Compliance with any DASH or diabetic diet for 12 weeks in patients with type 2 diabetes had beneficial effects on cardiometabolic risks.